EKSPLORASI ORNAMEN JEPARA DAN LAMBANG KERATON YOGYAKARTA SEBAGAI PENERAPAN PADA ARCHITRAVE - Ariyanto Ariyanto (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Jepara is the largest furniture industry city in Indonesia. There is a history since it was governed by Queen Kalinyamat (1521-1546), Jepara city was already known as the city of carving. The development of craft art in Jepara is increasing rapidly since R.A. Kartini. She also took part into art especially crafting art. She also helped to develop arts in creating new designs that have never been created by Jepara carving artist artists especially in making product of Architrave. But time by time the Architrave industry in Jepara is less developed due to the limitations of industry players to create new designs and only produce Architrave products that already exist in the market. After understanding the processes that occur in various types of Architrave industry in Jepara, then the authors do the design process using the method of exploration and incorporate element of Jepara culture and the symbol of the Palace of Yogyakarta. So it can bring new designs to compete in the growing architrave industry competition in the world. Jepara ornaments are ornnaments Nusantara which is often used for all kinds of Architrave for Jepara ornaments when carved unlike other ornaments. Leaf shape, niches, fruit when carved concave and convex very valuable aesthetic high, so from that many art lovers often use Exploration of ornament Jepara. Architrave is an ornament on the skin layer of both sills which provides aesthetic value added so that a room seemed beautiful to achieve the architrave must be based on research and a very deep study and takes a fairly long time, therefore architrave must be completely conceptualized